Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV MARIA S. MERIAN during cruise MSM117 - Rebecca Hummels; Mia Schumacher (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV MARIA S. MERIAN during cruise MSM117 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 2023-05-10 - 2023-06-15 from Recife (Brasil) to Ponta Delgada (Azores) in the Central and Northern Atlantic Ocean. Data were recorded in the EEZs of Brasil and Cape Verde and outside. MSM117 focused on investigating the variability of the western boundary current circulation off South America and to estimate the strength and variability of the Atlantic meridional overturning circulation (AMOC) at 11°S. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project and are according to the FAIR principles.